Dual-Continuum Design Approach for Intuitive and Low-Cost Upper Gastrointestinal Endoscopy - Garbin, Nicolo (IEEE Trans Biomed Eng, 2018)
OBJECTIVE: This paper introduces a methodology to design intuitive, low-cost, and portable devices for visual inspection of the upper gastrointestinal tract. METHODS: The proposed approach mechanically couples a multi-backbone continuum structure, as the user interface, and a parallel bellows actuator, as the endoscopic tip. Analytical modeling techniques derived from continuum robotics were adopted to describe the endoscopic tip motion from user input, accounting for variations in component size and pneumatic compressibility. The modeling framework was used to improve intuitiveness of user-to-task mapping. This was assessed against a 1:1 target, while ease-of-use was validated using landmark identification tasks performed in a stomach simulator by one expert and ten non-expert users; benchmarked against conventional flexible endoscopy. Pre-clinical validation consisted of comparative trials in in-vivo porcine and human cadaver models. RESULTS: Target mapping was achieved with an average error of 5° in bending angle. Simulated endoscopies were performed by an expert user successfully, within a time comparable to conventional endoscopy (<1 minute difference). Non-experts using the proposed device achieved visualization of the stomach in a shorter time (9s faster on average) than with a conventional endoscope. The estimated cost is <10 USD and <30 USD for disposable and reusable parts, respectively. SIGNIFICANCE AND CONCLUSIONS: Flexible endoscopes are complex and expensive devices, actuated via non-intuitive cable-driven mechanisms. They frequently break, requiring costly repair, and necessitate a dedicated reprocessing facility to prevent cross contamination. The proposed solution is portable, inexpensive, and easy to use, thus lending itself to disposable use by personnel without formal training in flexible endoscopy.